Lessons in radical innovation : out of the box, straight to the bottom line - Grulke, Wolfgang (Financial Times Prentice Hall, 2003)
Companies don't innovate - people do! With today's markets changing at warp-speed, no existing business believes it has a future without a strong focus on innovation. Companies with bold leadership are attempting to create a culture in which innovation can flourish. To do so, they need radical innovators and business activists. This is what Lessons in Radical Innovation is about. There are many books on innovation, but this is the first to take the debate from the corporate level to the individual. It's about real people who took risks, who set themselves extraordinary goals against almost impossible odds. These are stories about out-of-the-box thinking; about passionate individuals and the different kinds of companies they created. The book provides a structured way to think about innovation and gives practical examples of how individuals are doing it. Share their ideas, attitudes and tools - real world examples of real people making a real difference - and build your own context for thriving as a business radical.